2022
DOI: 10.1002/hyp.14566
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology and thermal regime of an ice‐contact proglacial lake: Implications for stream temperature and lake evaporation

Abstract: The formation of lakes as glaciers retreat can potentially influence stream temperature and enhance catchment water losses via evaporation. This study quantified the summer water and energy budgets and thermal regime of an ice‐contact proglacial lake below Bridge Glacier, British Columbia, to link ongoing glacier retreat with downstream effects. The ice‐proximal and distal portions of the lake behave differently due to a mid‐lake recessional moraine, against which icebergs are pinned by the dominant katabatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…However, lake surface and downstream river temperatures did begin warming in association with a decline in iceberg density following its peak in around 2012, even though the glacier remained lake terminating. As explained by Bird et al (2022), a decrease in iceberg density in the proximal basin would promote warming by resulting in a greater water surface area over which energy inputs to the lake water column could occur, as well as by reducing the transfer of heat from the water column to the icebergs to drive subaqueous melting. In addition, Bird et al (2022) observed that a 'wall' of icebergs was typically pinned against the submerged moraine by the dominant katabatic winds, and that water flowing through this wall from the proximal to the distal basin was cooled to about 0.9 C. In more recent years, this wall has been less continuous or even absent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, lake surface and downstream river temperatures did begin warming in association with a decline in iceberg density following its peak in around 2012, even though the glacier remained lake terminating. As explained by Bird et al (2022), a decrease in iceberg density in the proximal basin would promote warming by resulting in a greater water surface area over which energy inputs to the lake water column could occur, as well as by reducing the transfer of heat from the water column to the icebergs to drive subaqueous melting. In addition, Bird et al (2022) observed that a 'wall' of icebergs was typically pinned against the submerged moraine by the dominant katabatic winds, and that water flowing through this wall from the proximal to the distal basin was cooled to about 0.9 C. In more recent years, this wall has been less continuous or even absent.…”
Section: Discussionmentioning
confidence: 99%
“…A potential contributing factor to lake surface warming is inflow from the tributary streams, particularly South Creek, which has been observed to reach temperatures of about 14 C, well above the F I G U R E 1 0 Time series of near-surface water temperature recorded by Bird et al (2022) at profile E (light blue line) and Landsatderived lake surface temperature at the outlet point (black circles), which is less than 100 m from profile E.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations